Reposition of lenalidomide as a radiation protector based on LINCS gene expression signatures and its preclinical validation - Qi Huang; Xiaoyao Yin; Hua Guan; Xin Huang; Bo Huang; Dafei Xie; Pingkun Zhou (Scientific Reports)
Abstract Ionizing radiation induces DNA damage and impairs genomic integrity, leading to cell death and tissue injuries or carcinogenesis. Medical radiation protectors are essential and necessary. However, there are limited radioprotectors in clinics, which can’t meet the growing demand for countering radiation emergencies. Traditional drug discovery approach has been proven expensive and risky. Computational drug repositioning provides an attractive strategy for radioprotector discovery. Here we constructed a systematic workflow to identify repositioning radioprotectors by comparison of biosimilarity between γ-ray and known medicines characterized by gene expression signatures from GEO and LINCS. Using enrichment scoring, medicines with negative scores were considered as candidates of revising or mitigating radiation injuries. Seven approved medicines were identified, and their targets enriched in steroid and estrogen metabolic, chemical carcinogenesis associated pathways. Lenalidomide, an approved medicine for multiple myeloma and anemia, was further verified as a promising potential radioprotector. It increases survival of mice after lethal doses of irradiation by alleviating bone marrow and intestinal injury in vivo, and inhibits apoptosis of cultured irradiated AHH- 1 and IEC- 6 cells in vitro. This study introduces rational drug repositioning to radiation medicine and provides viable candidates for radioprotective therapeutic regimens.